Regulating financial networks under uncertainty - Carlos Ramírez (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2020)
I study the problem of regulating a network of interdependent financial institutions that is prone to contagion when there is uncertainty regarding its precise structure. I show that such uncertainty reduces the scope for welfare-improving interventions. While improving network transparency potentially reduces this uncertainty, it does not always lead to welfare improvements. Under certain conditions, regulation that reduces the risk-taking incentives of a small set of institutions can improve welfare. The size and composition of such a set crucially depend on the interplay between (i) the (expected) susceptibility of the network to contagion, (ii) the cost of improving network transparency, (iii) the cost of regulating institutions, and (iv) investors' preferences.
Keywords: C6; E61; G01; 330; Financial networks; contagion; policy design under uncertainty